2017
DOI: 10.20452/pamw.4107
|View full text |Cite
|
Sign up to set email alerts
|

High‑sensitivity troponin T as a prognostic marker in patients undergoing aortic valve replacement

Abstract: using EuroSCORE II. On the day before surgery, blood samples for the measurement of biomarker levels were collected from each patient. Complete blood count was performed with K 2 -EDTA samples, using a Cobas 6000 electronic counter (Roche, Mannheim, Germany). The plasma levels of cardiac TnT (cTnT) concentrations were measured by the Troponin T hs -STAT (Roche). The endpoint was all-cause death. Patients were followed by direct observation during hospitalization, telephone interviews, or clinic visits for 30 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 1 publication
1
11
0
Order By: Relevance
“…The predictive power of the preoperative TnT for death in 30-days follow-up in a group of 224 patients with surgically treated severe aortic stenosis was previously demonstrated [9]. Moreover, in a small group of 60 patients with severe aortic valve stenosis undergoing aortic surgery, preoperative TnT was an important predictor of serious post-operative complications in long-term follow-up [21].…”
Section: Aementioning
confidence: 86%
See 1 more Smart Citation
“…The predictive power of the preoperative TnT for death in 30-days follow-up in a group of 224 patients with surgically treated severe aortic stenosis was previously demonstrated [9]. Moreover, in a small group of 60 patients with severe aortic valve stenosis undergoing aortic surgery, preoperative TnT was an important predictor of serious post-operative complications in long-term follow-up [21].…”
Section: Aementioning
confidence: 86%
“…Moreover TnT is a recognized biomarker of myocardial injury [1]. In the available literature, several studies have reported that elevated high-sensitivity TnT (hs-TnT) is associated with poor outcomes in patients with stable coronary heart disease, acute myocardial infarction (MI), heart failure (HF), dilated cardiomyopathy, atrial fibrillation or significant aortic stenosis [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, TnT detected in plasma is a highly specific marker of myocardial injury [14][15][16]. To date, numerous publications have demonstrated a significant relationship between higher troponin values and worse prognosis in patients with acute myocardial infarction, heart failure or severe aortic valve disease [9][10][11][12][13]. It has also been described that TnT is a predictor of cardiac death in patients with CAD, atrial fibrillation or impaired left ventricular function [17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to this, after obtaining specific monoclonal antibodies, it became possible to use them in the diagnosis of ischemia and hypoxia of cardiomyocytes [8]. In the available literature, numerous articles describe high sensitivity troponin T (hs-TnT) as a biomarker of predictive importance in various diseases of the cardiovascular system, such as heart failure, coronary artery disease (CAD) and aortic stenosis [9][10][11][12][13]. The usefulness of the hs-TnT as a predictor of perioperative SCA in patients with valve disease undergoing valve surgery is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the present study indicate that the ongoing inflammatory process is associated with worse work of individual organs and systems, as indicated by the significant correlation demonstrated between CRP and haemoglobin, RDW, LVEF, TnT, creatinine and BMI parameters, which may have a decisive effect on the cardiosurgical treatment. And although fairly good calibration and discrimination of the EuroSCORE II calculator have been confirmed in the group of Polish patients undergoing cardiac surgery, information about the predictive ability of the CRP parameter may be useful for doctors both during the process of qualifying patients for cardiac surgery and in the postoperative period during patient care in intensive care unit therapy [2,22,23].…”
Section: -Specificitymentioning
confidence: 99%